Burden of hepatitis E virus infection in pregnancy and maternofoetal outcomes: a systematic review and meta-analysis - Jean Joel Bigna; Abdou Fatawou Modiyinji; Jobert Richie Nansseu; Marie A. Amougou; Moise Nola; Sébastien Kenmoe; Elvis Temfack; Richard Njouom (BMC, 2020)
Abstract Background There is still a dearth of knowledge on the burden of HEV infection in the global population of pregnant women. Therefore, we conducted a systematic review and meta-analysis to estimate the global burden of HEV infection in pregnancy. Methods We searched PubMed, Embase, Web of Knowledge, and Global Index Medicus to identify articles published until January 26, 2020. We considered cross-sectional, case-control, and cohort studies reporting the immunoglobulins M HEV seroprevalence in asymptomatic and symptomatic (jaundice or elevated transaminases) pregnant women or investigating the association between HEV infection and maternofoetal outcomes. We used a random-effects model to pool studies. This review was registered with PROSPERO, CRD42018093820. Results For HEV prevalence estimates, we included 52 studies (11,663 pregnant women). The seroprevalence was 3.5% (95% confidence interval: 1.4-6.4) in asymptomatic women (most of whom from high endemic areas). The prevalence in symptomatic women was 49.6% (42.6-56.7) with data only from HEV high endemic countries. In the multivariable meta-regression model, the prevalence was higher in symptomatic women compared to asymptomatic (adjusted prevalence odds ratio [aPOR]: 1.76; 95%CI: 1.61-1.91) and decreased with increasing year of publication (by 10-year) (aPOR: 0.90; 95%CI: 0.84-0.96). The proportion of HEV vertical transmission was 36.9% (13.3-64.2). Risk of bias was low, moderate and high respectively in 12 (23%), 37 (70%), and 4 studies (7%) addressing HEV prevalence estimation. HEV infection was associated with maternal deaths (pooled OR 7.17; 3.32-15.47), low birth weight (OR: 3.23; 1.71-6.10), small for gestational age (OR: 3.63; 1.25-10.49), preterm < 32 weeks (OR: 4.18; 1.23-14.20), and preterm < 37 weeks (OR: 3.45; 2.32-5.13), stillbirth (OR: 2.61; 1.64-4.14), intrauterine deaths (OR: 3.07; 2.13-4.43), and not with miscarriage (OR: 1.74; 0.77-3.90). All studies which assessed the association between HEV infection and maternofoetal outcomes had a moderate risk of bias. Conclusions Findings from this study are suggestive of a high burden of HEV infection in pregnancy in high endemic countries, its association with poor maternofoetal outcomes, and a high rate of vertical transmission. This study supports the need for specific strategies to prevent exposure of pregnant women to HEV infection, especially in high endemic areas.